2012
DOI: 10.2174/138161212803307527
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Cardiovascular Risk

Abstract: Fruits and vegetables (typically associated with the Mediterranean diet) are very rich in carotenoids, i.e. fat-soluble pigments really important in human life. Structurally, carotenoids consists of eleven (beta-carotene, zeaxanthin, lycopene) or ten (alpha-carotene, lutein) conjugated double bonds, responsible for their antioxidant capability in agreement with their substituents. Low-Density Lipoprotein (LDL) particles oxidation process is the one of the most important first steps of atherosclerotic disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Besides, human studies have concluded that carotenoids may prevent cardiovascular pathologies, which is supported by different observations, control‐case, prospective, and cross‐sectional population‐based studies. Thus, they have revealed an association between carotenoid serum levels and reduction of endothelial dysfunction, inflammation, and progression of atherosclerotic plaque (hardened lipids reducing artery and vein lumen; and therefore reducing, and even blocking, normal blood flow), which is probably due to a reduced oxidation of LDL, and is in agreement with several health benefits associated to carotenoids, as decreased lipid peroxidation and DNA damage, maintained immune function and inhibited malignant transformation or proliferation in vitro. This way, carotenoids have pleiotropic beneficial effects for health, preventing development of some diseases partially associated to aging.…”
Section: Introductionsupporting
confidence: 60%
“…Besides, human studies have concluded that carotenoids may prevent cardiovascular pathologies, which is supported by different observations, control‐case, prospective, and cross‐sectional population‐based studies. Thus, they have revealed an association between carotenoid serum levels and reduction of endothelial dysfunction, inflammation, and progression of atherosclerotic plaque (hardened lipids reducing artery and vein lumen; and therefore reducing, and even blocking, normal blood flow), which is probably due to a reduced oxidation of LDL, and is in agreement with several health benefits associated to carotenoids, as decreased lipid peroxidation and DNA damage, maintained immune function and inhibited malignant transformation or proliferation in vitro. This way, carotenoids have pleiotropic beneficial effects for health, preventing development of some diseases partially associated to aging.…”
Section: Introductionsupporting
confidence: 60%
“…Nutraceuticals are effectively able to reduce the burden of the atherosclerosis process and coronary heart disease development as already demonstrated in the literature (Ciccone et al, 2013;Garcia-Rios et al, 2013;Giordano et al, 2012;Kukongviriyapan et al, 2012;Kumar et al, 2012;Mitjavila & Moreno 2012;Raatz et al, 2013;Sheikholeslami Vatani & Ahmadi KaniGolzar, 2012;Voloshyna, Hussaini, & Reiss, 2012;Zhang et al, 2013). The main mechanisms that explain such a positive action on the cardiovascular system are not well understood.…”
Section: Nutraceutical Actions In Cardiovascular Diseasesmentioning
confidence: 99%
“…The main mechanisms that explain such a positive action on the cardiovascular system are not well understood. Carotenoids, the fat-soluble pigments produced by plants and microorganisms and highly present in fruits, vegetables, seaweeds and some seafoods and a fundamental component of Mediterranean foods, are already known to decrease the incidence and prevalence of cardiovascular events, perhaps by means of their antioxidant action on free radicals or by acting as anti-inflammatory molecules (i.e., by modulating the lipoxygenase enzyme activity) (Giordano et al, 2012). Izzo et al (2010) found amelioration in calculated Framingham Risk Score in patients suffering from metabolic syndrome and undergoing nutraceutical administration.…”
Section: Nutraceutical Actions In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some culture/stress conditions the microalga appears yellow or orange due to the presence of secondary pigments (carotenoids). These carotenoids are of high value, for example the astaxanthin is recognized as a potential anti-oxidant, and could prevent cancer and cardio-vascular problems [11,12]. The high productivity of the microalga Spirogyra sp.…”
Section: Introductionmentioning
confidence: 99%